The implication of nonradiative energy fluxes dominating Greenland ice sheet exceptional ablation area surface melt in 2012. Issue 6 (16th March 2016) - Fausto, Robert S.; van As, Dirk; Box, Jason E.; Colgan, William; Langen, Peter L.; Mottram, Ruth H.
Abstract: During two exceptionally large July 2012 multiday Greenland ice sheet melt episodes, nonradiative energy fluxes (sensible, latent, rain, and subsurface collectively) dominated the ablation area surface energy budget of the southern and western ice sheet. On average the nonradiative energy fluxes contributed up to 76% of daily melt energy at nine automatic weather station sites in Greenland. Comprising 6% of the ablation period, these powerful melt episodes resulted in 12–15% of the south and west Greenland automatic weather station annual ablation totals. Analysis of high resolution ( 5 km) HIRHAM5 regional climate model output indicates widespread dominance of nonradiative energy fluxes across the western ablation area during these episodes. Yet HIRHAM5 still underestimates melt by up to 56% during these episodes due to a systematic underestimation of turbulent energy fluxes typical of regional climate models. This has implications for underestimating future melt, when exceptional melt episodes are expected to occur more frequently. Key Points: Detailed observations of exceptional daily melt rates on the Greenland ice sheet in July 2012 We show this exceptional melt was dominated by nonradiative energy fluxes Conventional models underestimate melt episodes dominated by nonradiative energy fluxes